2021
DOI: 10.1038/s41467-021-27607-8
|View full text |Cite
|
Sign up to set email alerts
|

Heterocellular OSM-OSMR signalling reprograms fibroblasts to promote pancreatic cancer growth and metastasis

Abstract: Pancreatic ductal adenocarcinoma (PDA) is a lethal malignancy with a complex microenvironment. Dichotomous tumour-promoting and -restrictive roles have been ascribed to the tumour microenvironment, however the effects of individual stromal subsets remain incompletely characterised. Here, we describe how heterocellular Oncostatin M (OSM) - Oncostatin M Receptor (OSMR) signalling reprograms fibroblasts, regulates tumour growth and metastasis. Macrophage-secreted OSM stimulates inflammatory gene expression in can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 86 publications
(131 reference statements)
0
44
0
Order By: Relevance
“…Interestingly, Dinca et al recently showed in invasive breast ductal carcinomas that OSM can induce LOXL2 expression, which in turn promotes an increase in ECM collagen I fibre crosslinking, leading to increased cell invasion 59. Likewise, Lee et al, recently demonstrated that MØ-secreted Osm induces inflammatory gene expression in CAFs, creating a pro-tumourigenic environment in PDAC 60. Interestingly, they also show that tumour cells implanted in Osm −/− mice displayed an epithelial-dominated morphology as well as reduced tumour growth and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Dinca et al recently showed in invasive breast ductal carcinomas that OSM can induce LOXL2 expression, which in turn promotes an increase in ECM collagen I fibre crosslinking, leading to increased cell invasion 59. Likewise, Lee et al, recently demonstrated that MØ-secreted Osm induces inflammatory gene expression in CAFs, creating a pro-tumourigenic environment in PDAC 60. Interestingly, they also show that tumour cells implanted in Osm −/− mice displayed an epithelial-dominated morphology as well as reduced tumour growth and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…This spatial link between hypoxia and iCAF enrichment in vivo together with our in vitro finding that hypoxia promotes iCAF induction, raises the possibility that hypoxia plays an active role in driving regional stromal heterogeneity. Notably, recent studies have observed a correlation between iCAF enrichment and immunosuppression [6, 10, 31], which warrants the investigation of the effects of hypoxia on CAF-immune crosstalk.…”
Section: Discussionmentioning
confidence: 99%
“…The apCAF population is characterized by MHC class II expression [3]. Previous studies suggested a tumor-restrictive role for myCAFs and a tumor-promoting role for iCAFs and demonstrated that these subpopulations have the potential to interconvert [3,[6][7][8][9][10]. Mechanisms underlying CAF heterogeneity and plasticity as well as different roles of individual CAF subsets in pancreatic tumorigenesis are only beginning to be understood.…”
Section: Introductionmentioning
confidence: 99%
“…They reveal that LOXL2 expression by PDAC cells is mediated in paracrine fashion by macrophage-secreted oncostatin M (OSM), and subsequently, show that macrophage depletion in vivo can reduce expression of OSM and LOXL2, alter collagen structure and reduce metastasis 4. These findings are supported by work from the Jørgensen lab, which described how macrophage-secreted OSM could reprogramme fibroblasts to drive a more tumourigenic TME and facilitate metastasis in vivo 12. Of course, the efficacy of macrophage depletion in this study, and others, is likely not due solely to LOXL2 reduction.…”
mentioning
confidence: 86%